Pelagonius and Latin veterinary terminology in the Roman Empire - Adams, J. N. (Studies in Ancient Medicine, 1995)
The language of Latin veterinary medicine has never been systematically studied. This book seeks to elucidate the pathological and anatomical terminology of Latin veterinary treatises, and the general linguistic features of Pelagonius as a technical writer. Veterinary practice in antiquity cannot be related directly to that of the modern world. In antiquity a man could claim expertise in horse medicine without ever passing an examination. Owners often treated their own animals. The distinction between 'professional' and layman was thus blurred, and equally the distinction between 'scientific' terminology and laymen's terminology was not as clear-cut as it is today. The first part of the book is devoted to some of the non-linguistic factors which influenced the terminology in which horse diseases and their treatment were described.